The Cyclical Development of Trypanosoma vivax in the Tsetse Fly Involves an Asymmetric Division - Ooi, Cher-Pheng; Schuster, Sarah; Cren-Travaillé, Christelle; Bertiaux, Eloise; Cosson, Alain; Goyard, Sophie; Perrot, Sylvie; Rotureau, Brice (Frontiers in Cellular and Infection Microbiology, 2016)
Trypanosoma vivax is the most prevalent trypanosome species in African cattle. It is thought to be transmitted by tsetse flies after cyclical development restricted to the vector mouthparts. Here, we investigated the kinetics of T. vivax development in Glossina morsitans morsitans by serial dissections over one week to reveal differentiation and proliferation stages. After 3 days, stable numbers of attached epimastigotes were seen proliferating by symmetric division in the cibarium and proboscis, consistent with colonisation and maintenance of a parasite population for the remaining lifespan of the tsetse fly. Strikingly, some asymmetrically dividing cells were also observed in proportions compatible with a continuous production of pre- metacyclic trypomastigotes. The involvement of this asymmetric division in T. vivax metacyclogenesis is discussed and compared to other trypanosomatids.